Molecular epidemiology study of programmed death ligand 1 and ligand 2 protein expression assessed by immunohistochemistry in extensive-stage small-cell lung cancer - Steiniche, Torben; Georgsen, Jeanette Baehr; Meldgaard, Peter; Deitz, Anne C.; Ayers, Mark; Pietanza, M. Catherine; Zu, Ke (Frontiers in Oncology, 2024)
Objectives Prevalence of tumor PD-L1 expression in extensive-stage small-cell lung cancer (ES-SCLC) is variable, and data on PD-L2 expression are limited. The prognostic values of these biomarkers are not well understood. The current study was conducted to address these data gaps. Methods A retrospective cohort study of Danish patients with histologically confirmed ES-SCLC and evaluable tumor samples who were receiving usual care before the introduction of immunotherapy was conducted. Protein expression of PD-L1 and PD-L2 was determined by immunohistochemistry (IHC) using the PD-L1 IHC 22C3 pharmDx assay and a PD-L2 IHC assay using a propriety mouse monoclonal antibody. A combined positive score (CPS) of ≥1 was used to define biomarker positivity. Kaplan-Meier plots and Cox proportional hazard models were employed to assess the relationship between PD-L1 and PD-L2 protein expression and OS. Results Among 80 patients, 31% (n=25) and 36% (n=29) had disease positive for PD-L1 and PD-L2, respectively. Overall, 85% (n=68) of patients had concordant PD-L1/PD-L2 status; 26% (n=21) had double positive disease (both PD-L1 and PD-L2 CPS ≥1) and 59% (n=47) had double negative disease (both PD-L1 and PD-L2 CPS <1). PD-L1 and PD-L2 positivity were each associated with longer OS (unadjusted hazard ratios [HRs], 0.35 [95% CI, 0.21−0.61] and 0.50 [95% CI, 0.31−0.82]); the associations persisted after adjustment for several known prognostic factors (HRs, 0.41 [95% CI, 0.22–0.75] and 0.44 [95% CI, 0.25–0.79] for PD-L1 and PD-L2 positivity, respectively). When evaluating OS in patients with double positive disease, unadjusted and adjusted HRs for double positive compared with double negative were similar to those with only PD-L1 or PD-L2 positivity (unadjusted HR, 0.36 [95% CI, 0.20–0.64]; adjusted HR, 0.36 [0.18−0.73]). Conclusion PD-L1 and PD-L2 positivity were observed in approximately one-third of assessed ES-SCLC tumor samples and were highly congruent. Patients with PD-L1 and PD-L2 positivity, alone or combined, were associated with longer OS, independent of other prognostic factors.